Modifikasi Pembentukan Algoritma Rc4 Cipher Dengan Metode Acak Mid-Square Technique Untuk Pengamanan Voice Chat - Noviansyah, Bambang (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
Technological developments and human lifestyles allow access to information systems in new ways, for example using online conversations (chat) via an internet connection, which is often in the form of text communication (text chat) or voice (voice chat). Instant messaging only became popular when the internet began to be widely used in the mid-1990s. Along with the human need for easy and fast communication, the application that can be used is Voice Chat which allows users to carry out voice communication. But the voice chat application is less secure because it is easily intercepted by other parties. Eavesdroppers can easily find out the contents of conversations in instant messaging and the lack of privacy for chat users. The RC4 algorithm has a weakness in its use to encrypt a message. The downside is that Vigenere can only perform encryption and decryption processes for short messages. One way that can be used is to make security for the voice chat application using the Mid-Square Technique algorithm